2017 ASEE Annual Conference &Amp; Exposition Proceedings
DOI: 10.18260/1-2--28944
|View full text |Cite
|
Sign up to set email alerts
|

The Assertion-Evidence Approach to Technical Presentations: Overcoming Resistance in Professional Settings

Abstract: The assertion-evidence (AE) approach to presentations is a non-traditional way [1-4] for engineers and scientists to share their work with their audiences. In short, the approach calls on presenters to build each talk on messages (not topic phrases), to support those messages with visual evidence (not bullet lists), and to explain that evidence by fashioning sentences on the spot (but only after planning and practice). Research shows that presentations with the AE approach lead to deeper understanding of the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…If a presenter continuously reads items from the slide, often happening in presentations with bulleted lists, eye contact with the audience will be lost. Third, the way that slides are designed affects how a listener comprehends a topic (Miller & Alley, 2017).…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…If a presenter continuously reads items from the slide, often happening in presentations with bulleted lists, eye contact with the audience will be lost. Third, the way that slides are designed affects how a listener comprehends a topic (Miller & Alley, 2017).…”
Section: Related Workmentioning
confidence: 99%
“…Based on prior research promoting the use of Assertion Evidence slides of presentations (Miller & Alley, 2017) , it was hypothesized that participants in the Assertion Evidence group would have a reduced cognitive load and an improved motivation, presentation self-efficacy and understanding of the presentation material compared to participants in the Traditional PowerPoint condition.…”
Section: Research Objectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Garner and Alley (2016) found that students instructed with Assertion-Evidence Design exhibited greater retention of grammatical concepts compared to those taught using traditional approaches. Another study by Miller & Alley (2017) revealed that elementary school students taught with Assertion-Evidence Design achieved higher scores on standardized tests than those taught through traditional methods. Conversely, Farrokhi & Sattarpour (2012) found that written corrective feedback in the context of Assertion-Evidence Design was instrumental in improving the grammatical accuracy of highly proficient writers.…”
Section: Research Gap and The Need For The Present Studymentioning
confidence: 99%
“…Moreover, research suggests that AED is particularly beneficial for students with learning difficulties. Miller & Alley (2017) conducted a study revealing that AED was more effective than traditional instruction in improving knowledge retention among students with dyslexia. Similarly, Hu & Wan (2014) found that AED effectively improved knowledge retention among students with attention deficit hyperactivity disorder (ADHD).…”
Section: Introductionmentioning
confidence: 99%